2001
DOI: 10.1098/rspb.2001.1594
|View full text |Cite
|
Sign up to set email alerts
|

Maternal androgens in black-headed gull ( Larus ridibundus ) eggs: consequences for chick development

Abstract: We tested the hypothesis that mother birds counterbalance the negative e¡ects of hatching asynchrony for later-hatched chicks by increasing the yolk androgen concentrations in consecutive eggs of their clutch. In doing so, they may adaptively tune each o¡spring's competitive ability and, thus, growth and survival. However, evidence in support of this hypothesis is contradictory. The yolk concentrations of maternal androgens in the eggs of black-headed gulls increase signi¢cantly with the laying order of the eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
402
4
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 383 publications
(428 citation statements)
references
References 38 publications
21
402
4
1
Order By: Relevance
“…Schwabl (1993Schwabl ( , 1996 showed in canaries that egg yolk contains maternal androgens that influence the competitive abilities of the chicks after hatching. Eggs of the blackheaded gull have been shown to contain high levels of androgens too (Groothuis and Schwabl, 2002;Eising, Eikenaar, Schwabl, and Groothuis, 2001) and the relatively high levels around hatching in a period that the chick is still using yolk may still be of maternal origin.…”
Section: Priming Effects Of Early Testosteronementioning
confidence: 99%
“…Schwabl (1993Schwabl ( , 1996 showed in canaries that egg yolk contains maternal androgens that influence the competitive abilities of the chicks after hatching. Eggs of the blackheaded gull have been shown to contain high levels of androgens too (Groothuis and Schwabl, 2002;Eising, Eikenaar, Schwabl, and Groothuis, 2001) and the relatively high levels around hatching in a period that the chick is still using yolk may still be of maternal origin.…”
Section: Priming Effects Of Early Testosteronementioning
confidence: 99%
“…Groothuis et al, 2005a). In some bird species, androgens deposited in the egg yolk have been found to increase competitive ability of chicks (correlative data in Schwabl, 1993; experimental data in Eising et al, 2001), chick begging (experimental data : Schwabl, 1996;Schwabl and Lipar, 2002;Eising and Groothuis, 2003;Boncoraglio et al, 2006;von Engelhardt et al, 2006) and growth (experimental data: Schwabl, 1996;Eising et al, 2001;Pilz et al, 2004;Navara et al, 2005Navara et al, , 2006Tschirren et al, 2005). In other studies, however, no positive effect of elevated yolk androgens on begging or growth was found (experimental data: Sockman and Schwabl, 2000;Andersson et al, 2004;Pilz et al, 2004;Uller et al, 2005;Saino et al, 2006), or the effect depended on offspring sex (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that yolk hormone levels correlate with circulating plasma hormone levels in the female (Canary, Schwabl, 1996a) and may vary adaptively with the speciesÕ reproductive strategy and social requirements (Cattle egret, Schwabl et al, 1997, Black-headed gulls: Eising et al, 2001Groothuis and Schwabl, 2002). Maternal yolk hormones influence the offspringÕs embryonic development (Eising et al, 2001), development of the hatching muscle (Redwinged blackbird, Lipar and Ketterson, 2000), begging behavior (Canary, Schwabl, 1996b, Eising and Groothuis, submitted), and nestling growth rate (Eising et al, 2001). Recently it has also been found that male and female producing eggs differ in the content of maternal androgens (Petrie et al, 2001).…”
Section: Introductionmentioning
confidence: 99%